Development of family medicine in Ukraine. (December 2013) - Kolesnyk, Pavlo; Švab, Igor
Abstract This article includes a personal history of a family physician working in Ukraine. In June 2012, Pavlo Kolesnyk, Ukrainian Assistant Professor and a Family Doctor was awarded the second Montegute Scholar grant and had the chance to attend the Wonca Europe Conference 2012 in Vienna. In many developed countries, family medicine is already well established. In Ukraine, which has the legacy of a socialist health care system the implementation of the discipline started only at the end of the last century. The changes in the health care system were of greater importance in primary care and family medicine. It gave greater decentralization of the health care system and supported investment in primary care. This article describes the development of family medicine in undergraduate and postgraduate education. Whilst family medicine is officially a priority of health care policy, there is still a long process ahead. Family medicine needs financial support from the government and doctor's wages have to be increased, to prevent this branch of medicine being unpopular among graduating medical students.